Предмет: Алгебра,
автор: АннаКоренина
Выразите sin^6(a)+cos^6(a) через cos(4a) и с объяснением плисс
Ответы
Автор ответа:
3
Решение
sin^6(a)+cos⁶(a) = (sin²a)³ + (cos²a)³ =
(sin²a + cos²a)*(sin⁴a - sin²acos²a + cos⁴a) =
= [(sin⁴a + 2sin²acos²a + cos⁴a) - 3sin²acos²a] =
(sin²a + cos²a)² - 3sin²acos²a =
= 1 - 3sin²acos²a = 1 - (3/4)*(2sinacosa)*(2sinacosa) =
= 1 - (3/4)*(sin²2a) = 1 - [(1 - cos4a)/2] =
= 1 - 3/8 + (3/8)*cos4a = 5/8 + (3/8)*cos4a = (1/8)*(3cos4a + 5)
sin^6(a)+cos⁶(a) = (sin²a)³ + (cos²a)³ =
(sin²a + cos²a)*(sin⁴a - sin²acos²a + cos⁴a) =
= [(sin⁴a + 2sin²acos²a + cos⁴a) - 3sin²acos²a] =
(sin²a + cos²a)² - 3sin²acos²a =
= 1 - 3sin²acos²a = 1 - (3/4)*(2sinacosa)*(2sinacosa) =
= 1 - (3/4)*(sin²2a) = 1 - [(1 - cos4a)/2] =
= 1 - 3/8 + (3/8)*cos4a = 5/8 + (3/8)*cos4a = (1/8)*(3cos4a + 5)
АннаКоренина:
[(sin⁴a + 2sin²acos²a + cos⁴a) - 3sin²acos²a] а откуда здесь появляется - 3sin²acos²a
Похожие вопросы
Предмет: Музыка,
автор: WorldNeyron
Предмет: Биология,
автор: irynatitenkova
Предмет: Математика,
автор: dariashilets
Предмет: Русский язык,
автор: zlatapro13
Предмет: Геометрия,
автор: CHUBCHHELA